A Case Report of Calcifying Pseudoneoplasm of the Neuraxis: An Incidental Finding After a Car Accident - Farahnaz Bidari ZEREHPOOSH; Mohammad SAMADIAN; Vahideh Sadat AZHARI; Maryam BARANGI; Kaveh EBRAHIMZADEH; Mahnaz HEIDARY (Türk Patoloji Dergisi, 2018)

(untitled)
Calcifying pseudoneoplasms of the neuraxis are rare, poorly understood lesions that can occur anywhere in the central nervous system without any age or sex predilection. Their pathogenesis is still controversial. Patients can present with various symptoms due to lesion location and only few cases have been discovered incidentally. We present a 25-year-old male referred to our hospital after a car accident. Computed tomography scan and magnetic resonance imaging was done because of the patient's head trauma and a calcified intracranial lesion was found and excised surgically. Pathologic evaluation of the specimen was consistent with the diagnosis of calcifying pseudoneoplasm of the neuraxis.